PARADOXES OF THE MODERN ECONOMIC SCIENCE - Kumekhov, K.K.; G. Danilochkina, N.; I. Flegantov, V.; V. Cherner, N. (Gênero & Direito, 2020)
The crisis of the economic science may be explained largely by several paradoxes making logical premises uncertain. Based upon the “methodological pluralism”, they do not explain many fundamental matters making classification and accumulation of knowledge impossible. Our study aims to reveal (analysing modern economic theories by modelling) the main reasons of this state of the economic science, explain them scientifically and suggest the ways to eliminate them. By monographic studies, comparison and modelling, we have formulated the content of the scientific approach, its elements and their hierarchy. We have revealed the ways to implement scientific research and substantiated the need for economic modelling based upon identified criteria, and to build governmental economic policies on scientific grounds. Our conclusions and suggested measures are singular in respect of their content. They enable to evaluate objectively-based methodic grounds of the economic science anew. We believe, that the article would be of interest to a wide circle of researches dealing in methodology and economic modelling